Numerical non-equilibrium and smoothing of solutions in the difference method for plane 2-dimensional adhesive joints = Nierównowaga numeryczna i wygładzanie rozwiązań w metodzie różnicowej dla dwuwymiarowych połączeń klejowych - Rapp, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the paper is related to problems with numerical errors in the finite difference method used to solve equations of the theory of elasticity describing 2-dimensional adhesive joints in the plane stress state. Adhesive joints are described in terms of displacements by four elliptic partial differential equations of the second order with static and kinematic boundary conditions. If adhesive joint is constrained as a statically determinate body and is loaded by a self-equilibrated loading, the finite difference solution is sensitive to kinematic boundary conditions.
Keywords: połączenie klejowe; liniowa teoria sprężystości; metoda różnic skończonych; błąd numeryczny; wygładzanie rozwiązań; zadanie brzegowe Dirichleta; adhesive joint; linear theory of elasticity; finite difference method; numerical errors; smoothing of solutions; Dirichlet boundary value problem